LA UNIÓN EUROPEA Y LA ESTRATEGIA INTERNACIONAL DE AYUDA AL DESARROLLO DE LAS NACIONES UNIDAS - Ugarte Vega Centeno, Máximo Alfredo (2012)
As much as it may seem to some, the transfer of 0.7% of GDP in aid to Third World development is not a new proposal. The United Nations Organization has long been championing the cause. This initiative has been, however, embraced by the different social sectors in the European Union and is still far from achieving the goal set by the UN. Try to analyze the characteristics of an issue that everyone has heard of, but few know of the status of development aid.